Mesin Pembentuk Karakter Bangsa dalam Perspektif Al-Qur’an - - Ade Jamarudin; - Imam Ghozali (STAIN Bengkalis, 2019)
The character of education will give color to national character education. Therefore, education is a transformation towards the best educational output. All of us as children of the nation are the result of education. Both through forging informal, formal and non-formal education which are the three types of education recognized in Indonesia. Our education is education that comes from heaven and is applied by looking at the reality of the earth. Qur'ani-based education is an education that will deliver people to the achievement of national peace in the future. As an intellectual, of course we don't think short that the Qur'an only discusses only regarding worship. However, all aspects of life are discussed in the Qur'an with perfectly.